2023
DOI: 10.3389/fcvm.2023.1205893
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial capacity of mitochondrial oxidative phosphorylation in response to prolonged electromagnetic stress

Abstract: IntroductionMitochondria are central energy generators for the heart, producing adenosine triphosphate (ATP) through the oxidative phosphorylation (OXPHOS) system. However, mitochondria also guide critical cell decisions and responses to the environmental stressors.MethodsThis study evaluated whether prolonged electromagnetic stress affects the mitochondrial OXPHOS system and structural modifications of the myocardium. To induce prolonged electromagnetic stress, mice were exposed to 915 MHz electromagnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…These contradictory data may be due to the use of different cell models, experimental protocols, and durations of EMF exposure. Indeed, we have recently demonstrated that at the metabolic level, long-term exposure to EMFs could affect mitochondrial oxidative machinery through modulating cardiac OXPHOS capacity in a mouse model [52]. The study indicated that exposure to a 915 EMF for 28 days promotes the cardiac respiratory capacity of mitochondria without compromising the structural integrity of the heart tissues in mice at the age of 9 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These contradictory data may be due to the use of different cell models, experimental protocols, and durations of EMF exposure. Indeed, we have recently demonstrated that at the metabolic level, long-term exposure to EMFs could affect mitochondrial oxidative machinery through modulating cardiac OXPHOS capacity in a mouse model [52]. The study indicated that exposure to a 915 EMF for 28 days promotes the cardiac respiratory capacity of mitochondria without compromising the structural integrity of the heart tissues in mice at the age of 9 months.…”
Section: Discussionmentioning
confidence: 94%
“…Mice were housed in groups of four in polycarbonate cages and were allowed free access to standard food and water. Temperature was controlled at 21 ± 2 • C. Two days before EMF exposure, mice were allowed to adapt to new environmental conditions (light was provided on a 12 h light-12 h dark cycle), as previously described [52]. Animals were randomly divided into two groups: the control sham (n = 10) and EMF (n = 10) groups.…”
Section: Animalsmentioning
confidence: 99%
“…It is now clear that electromagnetic fields, such as from rotating magnets, can profoundly influence mitochondrial function, for instance, as an approach to kill cancer cells 53 , or at low intensities (10 µT) and low frequency (1–8 Hz) to induce mitophagy and rejuvenate mitochondrial function 54 . Other data also suggest that prolonged EMF can enhance cardiac and osteogenic mitochondrial function—the proposed mechanism involving a mild production of ROS and possibly complex I involvement 55 , 56 . Interestingly, earlier work showed that magnetic fields could affect the enzyme activity of horseradish catalysed oxidation of NADH.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of proteins from cardiac tissues was performed as previously described [ 29 ]. In short, we used RIPA buffer for protein extraction, and the lysates were quantified after clarification using the Bio-Rad Protein Assay (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%